2005
DOI: 10.1210/en.2004-1560
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate-Induced Interleukin 6 Production Is Mediated by Protein Kinase C and Nuclear-Factor κB Activation and Leads to Glucose Transporter 4 Down-Regulation in Skeletal Muscle Cells

Abstract: The mechanisms by which elevated levels of free fatty acids cause insulin resistance are not well understood. In addition, accumulating evidence suggests a link between inflammation and type 2 diabetes. Here, we report that exposure of C2C12 skeletal muscle cells to 0.5 mm palmitate results in increased mRNA levels (3.5-fold induction; P < 0.05) and secretion (control 375 +/- 57 vs. palmitate 1129 +/- 177 pg/ml; P < 0.001) of the proinflammatory cytokine IL-6. Palmitate increased nuclear factor-kappaB activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 48 publications
8
95
0
2
Order By: Relevance
“…These data seem to rule out the involvement of PKC activation in palmitate-mediated PGC-1␣ downregulation in skeletal muscle cells. Finally, since we have recently reported that skeletal muscle cells exposed to palmitate secrete IL-6 into culture media (19), and that this IL may affect cell metabolism, we determined whether IL-6 was involved in palmitate-mediated PGC-1␣ downregulation using an anti-IL-6 antibody. While treatment with palmitate led to a reduction in PGC-1␣ mRNA levels, coincubation with anti-IL-6 antibody did not prevent this change (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data seem to rule out the involvement of PKC activation in palmitate-mediated PGC-1␣ downregulation in skeletal muscle cells. Finally, since we have recently reported that skeletal muscle cells exposed to palmitate secrete IL-6 into culture media (19), and that this IL may affect cell metabolism, we determined whether IL-6 was involved in palmitate-mediated PGC-1␣ downregulation using an anti-IL-6 antibody. While treatment with palmitate led to a reduction in PGC-1␣ mRNA levels, coincubation with anti-IL-6 antibody did not prevent this change (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of mRNA. Levels of PGC-1␣ and -␤ mRNA were assessed by RT-PCR, as previously described (19). Total RNA was isolated by using the Ultraspec reagent (Biotecx, Houston).…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, palmitic and stearic acids are known to be major fatty acids acylated in the lipoprotein or lipopeptide to activate TLR2 [31,32]. NEFA possess the capacity to induce stress/inflammatory signals not only in immune cells but also other cell types and tissues [13,14,33]. This phenomenon is of particular importance in conditions of nutrient excess such as obesity and diabetes or after ingestion of a fatty meal.…”
Section: Discussionmentioning
confidence: 99%
“…NEFAs and triacylglycerols are elevated in obese and diabetic individuals and animals. Previous studies demonstrated that exposure to elevated NEFA causes activation of inflammatory signals and production of cytokines in multiple cell types, and these findings have been correlated with impairments of insulin actions [13,14]. Thus, circulating lipid and associated inflammation appear to be a link between nutrient excess and insulin resistance.…”
Section: Introductionmentioning
confidence: 95%
“…69 High levels of free fatty acids impair glucose and lipid metabolism 69 and induce the expression of proinflammatory cytokines in adipocytes, but this may not be a generalized effect of all fatty acids. Palmitate, but not laurate or docosahexanoic acid (DHA), induces IL-6 in adipocytes, 70 skeletal muscle cells 71 and endothelial cells. 72 Palmitate, but not other plasma-free fatty acids, correlates in vivo with IL-6 concentrations, independent of body fat mass.…”
Section: Subclinical Inflammationmentioning
confidence: 99%